Kegiatan Literasi Dan Numerasi Pada Program Kampus Mengajar Di SDN 3 Arjowilangun - Cholis Hidayati; Nandhita Kirana Atikasari (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The Teaching Campus Program is a form of implementation of the Merdeka Belajar Kampus Merdeka (MBKM) which is an opportunity for students to assist the learning process in elementary schools in various villages/cities, one of which is SDN 3 Arjowilangun. In this program, students who are involved have the responsibility of assisting the school in various ways, some of which include the teaching process, assisting with technology adaptation, and assisting with administration. In addition, students have the responsibility to improve student character and increase student learning interest during the assignment